Implementasi Desain Barang dan Jasa Pada UMKM Bakso dalam Meningkatkan Kepuasan Konsumen - Rika Nurjanah; Vania Camila; Olivia Nur Aini; M.Zahir Hamdani; Cristian Risky P (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Increasing competition in the culinary business encourages Micro, Small, and Medium Enterprises (MSMEs) to develop products and services that meet customer needs and improve customer satisfaction. This study aims to analyze the implementation of goods and service design in a family-owned meatball business as an application of Operations Management concepts to enhance business competitiveness. The research employed a descriptive qualitative approach using direct observation and interviews with the business owner as data collection techniques. The findings indicate that product design is implemented through the selection of high-quality raw materials, consistent meatball sizes, menu variations, and simple yet functional presentation. Service design is reflected in friendly customer service, fast serving processes, maintaining business cleanliness, and establishing good communication with customers. However, several aspects still need improvement, including packaging innovation, stronger brand identity, and greater utilization of digital marketing. Overall, the implementation of effective goods and service design has been proven to improve customer satisfaction, encouragecustomer loyalty, and strengthen the competitiveness of the business in an increasingly competitive culinary market.